"I don't want them to think that what they said matters": How treatment ‐ seeking adolescents with severe obesity cope with weight‐based victimization. Issue 3 (14th January 2021) - Walsh, Órla; Dettmer, Elizabeth; Regina, Andrea; Ye, Linlei; Christian, Jennifer; Hamilton, Jill; Toulany, Alene
Summary: Adolescents with severe obesity are subject to a high prevalence of weight‐based victimization that may lead to pervasive mental health symptoms. However, different coping strategies could potentially modulate these psychological consequences. This study aims to explore how treatment‐seeking adolescents with severe obesity cope with weight‐based victimization. This was a qualitative research study using an interpretive phenomenological analytic approach. One‐on‐one semi structured interviews were completed with 19 adolescents (63% female) enrolled in a weight management program. The interviews were transcribed and sequentially analysed until data saturation was attained. The majority of participants (89.5%) described being a victim of weight‐based victimization and highlighted a significant emotional toll. Two key themes were identified that captured the various coping strategies used by participants. Over half (52.9%) described approach coping strategies where they acted on the source to invoke change by standing up for themselves, helping others in similar situations or becoming a bully themselves. Whilst the majority (94.1%) used avoidant coping strategies such as feigning a strong exterior façade, denial, isolation and self‐harm. Nearly half (47.1%) used both strategies. Treatment‐seeking adolescents with severe obesity commonly use avoidant coping strategies to deal with weight‐based victimization. These strategies are associated with negative mental health outcomes and should be evaluated when counselling adolescents with obesity who have experienced weight‐based victimization.